LREE of a dressed Dp-brane with transverse motion in the partially compact spacetime - Hamidreza Daniali; Davoud Kamani (Journal of High Energy Physics)
Abstract In the context of the type IIA/IIB superstring theories, we derive the left-right entanglement entropy (LREE) of a BPS Dp-brane with transverse motion in the presence of a U(1) gauge potential and the Kalb-Ramond field in the partially compact spacetime T n ⊗ ℝ 1,9 − n . At first we employ the replica trick to compute the Rényi entropy and then we obtain the entanglement entropy. We examine the results for the special case, i.e. for the D6-brane. Besides, we investigate the thermodynamical entropy, associated with the LREE. This demonstrates that the LREE is precisely equivalent to its thermodynamic counterpart.